Musicality in Infancy - Sandra E. Trehub (Psychological Topics, 2023)
The present review summarizes the available evidence on musicality, or music-related abilities, in infants (birth to 3 years). In the early months of life, infants are responsive to the pitch and temporal patterns of music. Their perceptual skills are similar, in many respects, to those of adults, presumably because of the nature of the human auditory system. Adult-infant differences, where evident, are attributable to infants’ unfamiliarity with the musical conventions of their culture. Musical enculturation proceeds more rapidly for temporal than for pitch processing. Musical exposure, especially the singing of caregivers, is prevalent in infancy. Caregivers’ music-making for infants has consequences for their emotional and social regulation and for their subsequent self-regulation abilities. By the end of their first year, most infants have become music-makers as well as music listeners. They move spontaneously to music, and their patterns of “dancing” undergo considerable change in the subsequent months and years. Early dancing is influenced by the familiarity of the music, and later dancing may include aspects of caregivers’ dance movements. Although the onset of singing occurs considerably later than the onset of dance, early singing is remarkably accurate in terms of its pitch range, pitch contours, rhythmic patterning, and fluency, especially when infants sing in their familiar home environment.